2011
DOI: 10.1158/0008-5472.can-10-3358
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase KMT1A Restrains Entry of Alveolar Rhabdomyosarcoma Cells into a Myogenic Differentiated State

Abstract: Alveolar rhabdomyosarcoma (ARMS) is an aggressive pediatric muscle cancer which arrested during the process of skeletal muscle differentiation. In muscle myoblast cells, ectopic expression of the histone H3 lysine 9 (H3K9) methytransferase KMT1A blocks differentiation by repressing a myogenic gene expression program. In this study, we tested the hypothesis that activation of a KMT1A-mediated program of transcriptional repression prevents ARMS cells from differentiating. We investigated whether KMT1A represses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…Differences in the response to the same treatment of RMS variants are not unusual and are in agreement with both the different cytogenetic and molecular background of fusion-positive alveolar RMS also related to the expression of PAX-FOXO1 chimeric proteins. 1,2,[61][62][63][64][65] Collectively, our data suggest that in PAX3-FOXO1 alveolar RMS EZH2 supports tumor cell survival at least in part by repressing FBXO32.…”
Section: (Student's T-test) (B) Ezh2mentioning
confidence: 62%
“…Differences in the response to the same treatment of RMS variants are not unusual and are in agreement with both the different cytogenetic and molecular background of fusion-positive alveolar RMS also related to the expression of PAX-FOXO1 chimeric proteins. 1,2,[61][62][63][64][65] Collectively, our data suggest that in PAX3-FOXO1 alveolar RMS EZH2 supports tumor cell survival at least in part by repressing FBXO32.…”
Section: (Student's T-test) (B) Ezh2mentioning
confidence: 62%
“…[25][26][27][28] Despite activated AKT pathway in ARMS cells, they are defective in terminal myogenic differentiation. 17,40,41 In ARMS, it is well recognized that PAX3-FKHR works by the gain of transcriptional power. 2,50,51 The present study was focused on deciphering the molecular mechanism underlying activated AKT signaling in association with PAX3-FKHR transactivation in the suppression of the myogenic differentiation program in ARMS.…”
Section: Discussionmentioning
confidence: 99%
“…18,21 Here, we show that mouse ARMS cells reflect the defective terminal myogenic phenotype as revealed by no sign of MyHC expression similar to their human counterpart under differentiation conditions (DM). 17,40,41 In this context, studies have implicated that impaired MyoD transcriptional activity-mediated myogenic gene expression, but not the absence of MyoD, is associated with the failure of ARMS cells to differentiate terminally. 31,42,52 However, the data here indicated that impaired MyoD transactivation function is coupled with decreased levels of MyoD when these ARMS cells are under DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations